COMPETENCY-BASED APPROACH TO THE FORMATION OF STUDENT YOUTH HEALTH IN UKRAINE - Бобрицька, В. І. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
. The article elucidates the key aspects of intellectual activity impacting (positively or negatively) on the health of student youth; specifies the causes which, in the learning activities of students, have a negative impact on their health and on acquiring unproductive experience of its formation during their studies at an institution of higher education; substantiates the strategic guidelines in application of the competency-based approach to the formation of the health of modern student youth in Ukraine